PENGARUH PENGGUNAAN LEAFLET SEBAGAI MEDIA PENDIDIKAN KESEHATAN TERHADAP KEPATUHAN TERAPI DAN PENURUNAN KADAR KOLESTEROL PASIEN HIPERKOLESTEROLEMIA DI PUSKESMAS TEGALREJO YOGYAKARTA - Yuliana Dewi Anggraini (PSF 15 UMY 612, 2015)
Low loyalty on therapy opration still being a problem in health sector. Which one in this situation often time not be accompanied high loyalty in this therapy called hypercolerterolemia. Hypercholesterolemia also constitude factor agen people died in young age. Based on data from World Healt Organization (WHO) in the year of 2002 recorded as much as 4,4 million death cause coronery heart disease is the result of hypercholesterolemia or as big 7,9% from the total number of deaths at a young age. This is a research study pre-experimental with methot one group pretest and posttest. Research was conducted to analyzethe effect of leaflet as health education media on patient compliance and decrease cholesterol level. Research conducted by measuring patient compliance in the treatment and diet, and measure the patients physical activity as an essential component in the management of state hypercholesterolemia. The sample of a patient at the healthcenter hypercholesterolemia. The sample is a patient at the health center hypercholesterolemia Tegalrejo Yogyakarta. Sample are taken with the technique consecutive sampling. Adherence to treatment was measured using kuisioner Morisky, where are compliance a diet and physical activity were measured using a questioneire of previous researchers. Total sample obtained in this research is 30 people.